Identification of antigen-specific neutrophils in the tonsils with recurrent acute inflammation. (3rd July 2020) - Zhou, Cai-Jie; Mo, Li-Hua; Luo, Xiang-Qian; Yang, Gui; Diao, Wei-Liang; Hu, Shi-Ping; Yang, Ping-Chang
Abstract: The pathogenesis of recurrent acute tonsillitis (Rtn) is to be further investigated. Polymorphonuclear neutrophils (PMN) often associate with the pathogenesis of acute and chronic inflammation. This study aims to identify the antigen-specific PMNs (sPMNs) isolated from the tonsillar tissues with recurrent acute inflammation. In this study, CD66b + PMNs were isolated from surgically removed tonsils (40 tonsils were from 20 Rtn patients; 24 tonsils were from 12 tonsil tumour patients) by flow cytometry cell sorting. sPMNs were identified through immunological approaches. We found that compared with the control tonsil samples (from marginal non-tumour tissues of tonsil cancer), Rtn samples showed higher PMN frequency, higher levels of myeloperoxidase (MPO) and neutrophil elastase (NE), in which positive correlation was detected between the inflammatory scores in the Rtn tissues and PMN counts ( r  = .7352; p  = .0002), or MPO ( r  = .6565, p  = .0017), or NE ( r  = .6687, p  = .0013). Upon exposure to tonsillar tissue protein extracts in the culture, a portion of Rtn PMNs was activated and released inflammatory mediators. A complex of tonsillar tissue-specific IgG and FcγRI was observed on the surface of Rtn PMNs; these PMNs could specifically recognize the Rtn tissue extracts and were designated the tonsillar antigen-specific PMNs (sPMNs). A signal transduction pathway of mitogen-activated protein kinase (MAPK)-nuclear factor of T cell activation (NFAT) was activated in sPMNs after exposure to Rtn tissue extracts. In summary, a fraction of sPMN in the Rtn tonsillar tissues was identified and characterized. The sPMNs can be activated upon exposure to tonsil-specific antigens. These sPMNs may contribute to the Rtn pathogenesis.